Predictors for rTMS response in chronic tinnitus - Lehner, Astrid; Schecklmann, Martin; Landgrebe, Michael; Kreuzer, Peter M.; Poeppl, Timm B.; Frank, Elmar; Vielsmeier, Veronika; Kleinjung, Tobias; Rupprecht, Rainer; Langguth, Berthold (Frontiers in Systems Neuroscience, 2012)
Background: Repetitive transcranial magnetic stimulation (rTMS) has been studied as a treatment option for chronic tinnitus for almost ten years now. Although most of these studies have demonstrated beneficial effects, treatment results show high interindividual variability and yet, little is known about predictors for treatment response. Methods: Data from 538 patients with chronic tinnitus were analysed. Patients received either low-frequency rTMS over the left temporal cortex (n= 345, 1 Hz, 110% motor threshold, 2000 stimuli/day) or combined temporal and frontal stimulation (n = 193, 110% motor threshold, 2000 stimuli at 20 Hz, left dorsolateral prefrontal cortex plus 2000 stimuli at 1 Hz, temporal cortex). Numerous demographic, clinical and audiological variables as well as different tinnitus characteristics were analysed as potential predictors for treatment outcome, which was defined as change in the tinnitus questionnaire (TQ) score. Results: Both stimulation protocols resulted in a significant improvement in TQ scores. In the group receiving combined treatment, patients with comorbid temporomandibular complaints benefited more from rTMS than patients without those complaints. In addition, for both stimulation protocols the TQ score at baseline as well as the change in TQ score from screening to baseline correlated significantly with treatment response. Patients with higher TQ scores at baseline had more pronounced TQ reductions than patients with low TQ baseline scores. Also, patients who had already improved from screening to baseline benefited less than patients without initial improvement. Conclusions: The results from this large sample confirm the effectiveness of rTMS for the treatment of chronic tinnitus. Nonetheless, the high interindividual variability in treatment response can only be partly explained by the investigated clinical variables.